DEVELOPING CUCUMBER CANDIDATE LINES BASED ON FRUIT SKIN COLOR - Muhammad Adelin Nazhirin; Rajiman, Rajiman; Elea Nur Aziza (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
This study aims to assemble cucumber strain candidates based on the diversity of fruit skin color. This research was conducted at Celeban Teaching Factory of Agricultural Development Polytechnic Yogyakarta-Magelang campus, Yogyakarta, Indonesia from February to June 2023. The research object consisted of two cucumber varieties as parental and two first derivatives or First Offspring lines from reciprocal crosses of two parental lines. The research method used a single-plant experiment by planting and observing each plant of the cross. The crossing was carried out by the double-cross method reciprocally to obtain two numbers of derivative plants, for each number planted as many as 80 plants so that there was a population of 160 derived plants and eight parental plants for each parental strain as a comparison. The parameters in this study included the intensity of green leaf color, the basic color of the fruit skin, the intensity degree of the basic color of the fruit skin, the tip shape of the fruit, the base form of the fruit and the cut of the crosscut fruit. The research’s results from the observed population obtained a diversity of fruit skin colors classified into 4 clusters of the candidate lines, namely bright yellow, bright green, medium green, and dark green fruit skin clusters.